Commercialization of Education and Academic Activities of Private Secondary Schools in Rivers East Senatorial Zone, Rivers State, Nigeria - Patience O. Emesiobi (PhD); Marilyn U. Ochoma (PhD) (Researchparks Publishing, 2022)
This study investigates commercialization of education and academic activities of private secondary schools in Rivers East Senatorial Zone, Nigeria. The descriptive survey design was adopted for the study. Two research questions and two hypotheses guided the study. The population of the study comprised all private secondary school teachers in four randomly selected local government areas in Rivers East Senatorial Zone, a total of 18,004. A sample size of 1798 teachers drawn from 10 schools from each of the four local government areas in Rivers East Senatorial Zone was used for this study. The instrument for data collection was a set of questionnaire titled: Commercialization of Education and Academic Activities of Private Secondary Schools Questionnaire (CEAAPSSQ). Face and content validity were carried out on the instrument as well as reliability test. A reliability coefficient of 0.86 was obtained. Mean and standard deviation were used to answer the research questions while t-test was used to test the hypotheses at 0.05 level of significance. The result of the study revealed among others that commercialization of education has positive influence on academic productivity in private schools. It was recommended that activities of private schools should be properly monitored and checkmated by the government to ensure that they measure up to expectations where necessary, at all times particularly in terms of quality of teachers and curriculum choice.